2001
DOI: 10.1080/713846825
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fatigue and Sexual Dysfunction in Female Gulf War Veterans

Abstract: Chronic fatigue (CF) is one of the most common conditions reported by Gulf War veterans. This study evaluated female sexual dysfunction (FSD) in veterans with or without complaints of CF. Subjects were screened for medical and psychiatric causes of CF. They included 22 healthy subjects and 26 with fatiguing symptoms. FSD was reported by 10% of controls and by 60% of the fatigued (p < .002) while 19% versus 81% (p < .001) noted decreased libido. FSD was more prevalent in fatigued veterans than in the controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
0
16
1
Order By: Relevance
“…We are aware of only one study that examined sexual functioning in combat-exposed women. Gilhooly, Ottenweller, Lange, Tiersky, and Natelson (2001) evaluated sexual dysfunction in a sample of female Persian Gulf War veterans with (n = 26) and without (n = 22) chronic fatigue syndrome (CFS) and found more sexual functioning difficulties in the CFS group. Because the study did not include a noncombat exposed control group, it did not directly examine the effect of combat on sexual functioning.…”
mentioning
confidence: 99%
“…We are aware of only one study that examined sexual functioning in combat-exposed women. Gilhooly, Ottenweller, Lange, Tiersky, and Natelson (2001) evaluated sexual dysfunction in a sample of female Persian Gulf War veterans with (n = 26) and without (n = 22) chronic fatigue syndrome (CFS) and found more sexual functioning difficulties in the CFS group. Because the study did not include a noncombat exposed control group, it did not directly examine the effect of combat on sexual functioning.…”
mentioning
confidence: 99%
“…Sexual health and functioning in general are an important consideration in our veteran population and appear to be a neglected area of clinical focus. Research indicates: (1) Both male and female veterans present to VA medical centers with sexual functioning concerns (Ackerman, D'Attilio, Antoni, & Campbell, 1991;Gilhooly, Ottenweller, Lange, Tiersky, & Natelson, 2001;Husain, Carwile, Miller, & Radtke, 1998;Plaud et al, 1996); and (2) sexual health is consistently identified by both male and female veterans as important (Mulligan & Moss, 1991;Nusbaum & Gamble, 2001;Nusbaum et al, 2004). However, medical providers are often unaware or inattentive to patient sexual health issues (Nusbaum & Gamble, 2001) and frequently fail to take a patient's sexual history or to initiate a discussion of sexual health needs (Ende, Rockwell, & Glasgow, 1984;Nusbaum & Gamble, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…() investigated sexual dysfunction in female Gulf War veterans and observed a significantly higher prevalence of sexual dysfunction in veterans with chronic fatigue. The loss of libido was the most crucial difference between veterans with chronic fatigue and those without chronic fatigue (Gilhooly et al ., ). Verneulen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic fatigue syndrome patients exhibit several comorbid conditions that affect their social and physical activity and sexual function (Blazquez et al ., ). Several studies on the association between women with CFS and sexual dysfunction have been conducted, but have yielded conflicting results (Gilhooly et al ., ; Vermeulen & Scholte, ). In contrast to female sexual dysfunction, male sexual dysfunction is easier to define and diagnose.…”
Section: Introductionmentioning
confidence: 99%